The performance dimension in symbolic management revisited: the functional role of traditional mechanisms in large Korean firms*. Issue 1 (1st January 2017) - Yoo, Taeyoung
Abstract: Symbolic management perspective argues that newly adopted shareholder-oriented mechanisms promote positive market responses, whereas traditional mechanisms assume sociopolitical power struggle for their sustainability. Beyond the dichotomous understanding, this study proposes that the continuation of traditional mechanisms is also attributable to their performance contribution. Using panel data on 100 large Korean firms (1998–2011), this study found that the positive influence of traditional mechanisms such as business group on performance, measured by ROA and R&D intensity, improves market responses, i.e. market capitalization and Tobin's q . In the process, shareholder-oriented mechanisms, such as foreign ownership, positively moderates the influence of traditional mechanisms. For corporate governance reform, this study suggests that balanced attention should be paid to the performance contribution of traditional mechanisms in interaction with shareholder-oriented mechanisms.